Frequency UWB Channel (2011)
Ultra wideband (UWB) transmission systems are characterized with either a fractional bandwidth of more that 20%, or a large absolute bandwidth (>500 MHz) in the 3.1 GHz to 10.6 GHz band, and for a very low power spectral density (-41.25 dBm/MHz, equivalent to 75nW/MHz), which allows to share the spectrum with other narrowband and wideband systems without causing interference (FCC, 2002), this spectral allocation has initiated an extremely productive activity for industry and academia. Wireless communications experts now consider UWB as available spectrum to be utilized with a variety of techniques and not specifically related to the generation and detection of short RF pulses as in the past (Batra, 2004). For this reason, UWB systems are emerging as the best solution for high speed short range indoor wireless communication and sensor networks, with applications in home networking, high-quality multimedia content delivery, radars systems of high accuracy, etc. UWB has many attractive properties, including low interference to and from other wireless systems, easier wall and floor penetration, and inherent security due to its Low Probability Interception/Detection (LPI/D). Two of the most promising applications of UWB are High Data Rate Wireless Personal Area Network (HDR-WPAN), and Sensor Networks, where the good ranging and geo-location capabilities of UWB are particularly useful and of interest for military applications (Molisch, 2005).